SULTANKU, MAHMUD BADARUDDIN II - Kemas A.R. Panji (Fakultas Adab dan Humaniora UIN Raden Fatah, 2013)
Abstract: Figure of Sultan Mahmud Badaruddin II ( SMB II ) is widely known especially after he was named National Hero and painting his picture made picture at Rp 10,000 bills by Bank Indonesia is the year 2005 , apparently the picture above just imagination . Was created as one of the requirements to be the leader of the Palembang Darussalam Sultanate was awarded the title of national hero . Masterpiece of a painter Palembang . SMB II , Born in Palembang on Sunday night , hours 9.00 ( 1 H Rejeb 1181 / February 9, 1768 AD ) . He 's boyhood named Raden Hasan bin Soeltan Moehammad Bahaoeddin , later designated as the heir to the title of Prince of Palembang Sultanate Queen . After he was crowned the Sultan of Palembang on December 22, 1218 H Zulhijjah dated 4 April 1803 coincided title of Sultan Mahmud Badaruddin the Queen or the Prince known as SMB II . In addition to the Sultan of Palembang He is Al - Hafiz ( Ulama ) in Palembang Darussalam Sultanate . Keywords : Sultan Mahmud Badaruddin II . Palembang Darussalam Sultanate